2003
DOI: 10.1210/en.2002-0031
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Stimulated Gene-15 (Isg15) Expression Is Up-Regulated in the Mouse Uterus in Response to the Implanting Conceptus

Abstract: An early response of the human and bovine endometrium to pregnancy is induction of an interferon (IFN)-stimulated gene (ISG) that encodes the ubiquitin-related protein, ISG15. Because the mode of implantation differs among species, we tested whether Isg15 mRNA was also expressed in the mouse uterus in response to the implanting conceptus. Isg15 mRNA was detected in the mouse uterus and increased after d 4.5 of pregnancy but did not change between d 3.5 and 9.5 of pseudopregnancy. Within the decidua, Isg15 mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 41 publications
(52 reference statements)
7
71
1
Order By: Relevance
“…Irf1 mRNA was most abundant in uteri of rats treated with both E 2 and IFNA. In support of findings of Li et al (2001), Austin et al (2004) and Bany & Cross (2006) reported that mouse trophoblast giant cells express IFNA that, in turn, induced expression of ISG15 during the peri-implantation period.…”
Section: Ifns and Uterine Receptivity To Implantation In Rodentssupporting
confidence: 78%
“…Irf1 mRNA was most abundant in uteri of rats treated with both E 2 and IFNA. In support of findings of Li et al (2001), Austin et al (2004) and Bany & Cross (2006) reported that mouse trophoblast giant cells express IFNA that, in turn, induced expression of ISG15 during the peri-implantation period.…”
Section: Ifns and Uterine Receptivity To Implantation In Rodentssupporting
confidence: 78%
“…Although the IFN-τ are unique to the Ruminantia, a sub-order within the much larger Artiodactyla order, there are hints from transcriptional profiling experiments that a partial interferon-response occurs in humans and mice as the trophoblast makes intimate contact with the maternal endometrium and induces the formation of a deciduum, in which stromal fibroblast proliferate and form an edematous structure adjacent to the site of implantation (37)(38)(39). This response does not involve a full-blown up-regulation of many interferon-stimulated genes (ISGs), as noted in the sheep endometrium during early pregnancy (12,13,40), but is instead more limited.…”
Section: Type 1 Ifn and Pregnancymentioning
confidence: 99%
“…Interferons (IFNA, IFNB, IFNG) are produced by placentae of mice as early as day 7 of pregnancy and several ISGs are expressed by cells in implantation sites (Austin et al, 2003;Bany and Cross, 2006). Expression of both IFNA and interferon-regulated gene 1 (IRG1) increase in uteri of pregnant rats between days 1 and 4 and then decrease following implantation.…”
Section: Pseudopregnancy and Pregnancymentioning
confidence: 99%